Metode Mengajar Guru Aqidah Akhlak Kelas VIII Di MTI Tarusan Kamang - Elma Rahma; Salmiwati Salmiwati (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research was motivated by the fact that the learning process of moral aqidah was less enjoyable for students, it was found that students were not focused on learning, chatting with friends and sleeping in class and also the values ​​contained in learning Aqidah Morals had not been implemented in the students' daily lives. Based on this background, the author formulates the problem, namely how teachers teach moral aqidah methods for class VIII and the supporting and inhibiting factors for implementing class VIII learning methods at Mti Tarusan Kamang. This research uses a qualitative approach, to collect data by means of interviews and observations. The results of the research show that there are five learning methods used by teachers in learning moral aqidah in class VIII, namely the lecture method implemented by the teacher by starting to formulate learning objectives, preparing material and assessment techniques. However, teachers do not have good strategies and communication in delivering material so that there are students who are not enthusiastic about the teacher's explanation. The question and answer method is only used by teachers as a complementary method in implementing the lecture method. The teacher implements the exemplary method by providing examples in accordance with the values ​​contained in the material, but in some circumstances there are some teacher behaviors that cannot be used as examples. The habituation method often occurs outside of class hours and is carried out by routinizing several positive activities, but in some situations it becomes neglected due to busy school activities and this habituation seems to force students. And finally, the story method is implemented by the teacher as a complement to the lecture method. The supporting factor for implementing the Aqidah Akhlak class VIII learning method is because this method is seen as capable of achieving the objectives of learning Aqidah Akhlak. Meanwhile, the inhibiting factors are the lack of teacher preparation before teaching in the form of learning equipment and media, as well as the lack of communication and cooperation between teachers and students' parents.